Composition-dependent structural characteristics and mechanical properties of amorphous SiBCN ceramics by ab-initio calculations - Liu, Yuchen (2023)
The atomic structural features and the mechanical properties of amorphous silicoboron carbonitride ceramics with 13 different compositions in the Si–BN–C phase diagram are investigated employing ab-initio calculations. Both chemical bonds and local structures within the amorphous network relate to the elemental composition. The distribution of nine types of chemical bonds is composition-dependent, where the B–C, Si–N, Si–C, and B–N bonds hold a large proportion for all compositions. Si prefers to be tetrahedrally coordinated, while B and N prefer sp2-like trigonal coordination. In the case of C, the tetrahedral coordination is predominant at relatively low C contents, while the trigonal coordination is found to be the main feature with the increasing C content. Such local structural characteristics greatly influence the mechanical properties of SiBCN ceramics. Among the studied amorphous ceramics, SiB2 C3N2 and SiB3 C2 N3 with low Si contents and moderate C and/or BN contents have high elastic moduli, high tensile/shear strengths, and good debonding capability. The increment of Si, C, and BN contents on this basis results in the decrease of mechanical properties. The increasing Si content leads to the increment of Si-contained bonds that reduce the bond strength of SiBCN ceramics, while the latter two cases are attributed to the raise of sp2-like trigonal configuration of C and BN. These discoveries are expected to guide the composition-tailored optimization of SiBCN ceramics.